2000
DOI: 10.1002/1097-0169(200008)46:4<269::aid-cm4>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar elongation induced by glucose limitation is preadaptive forTrypanosoma cruzi differentiation

Abstract: Trypanosomes must sense and respond to environmental change in order to progress through their life cycles. The American trypanosome, Trypanosoma cruzi, differentiates from the noninfective epimastigote form to the infective metacyclic form spontaneously in axenic culture. Here, we investigate the initial stimulus for that change and demonstrate that T. cruzi epimastigotes sense limitation of glucose in the medium and respond by undergoing significant morphological and biochemical change. As part of this chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 31 publications
1
28
0
4
Order By: Relevance
“…Assays to examine whether the product release from the parasite during pre-incubation phase, are involved in the inhibition of the morphological transformation are in progress and might be useful to explain why the metacyclic trypomastigote can also escape from endocytic vacuole into the host cell cytoplasm (Dvorak 1975). Tyler and Engman (2000) have shown that the depletion of glucose from the medium triggers elongation of the epimastigotes flagellum. Later, the authors proposed that the intracellular glucose concentration is the key factor for both elongation of the flagellum and sustaining the differentiation of the metacyclic trypomastigote (Tyler & Engman 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Assays to examine whether the product release from the parasite during pre-incubation phase, are involved in the inhibition of the morphological transformation are in progress and might be useful to explain why the metacyclic trypomastigote can also escape from endocytic vacuole into the host cell cytoplasm (Dvorak 1975). Tyler and Engman (2000) have shown that the depletion of glucose from the medium triggers elongation of the epimastigotes flagellum. Later, the authors proposed that the intracellular glucose concentration is the key factor for both elongation of the flagellum and sustaining the differentiation of the metacyclic trypomastigote (Tyler & Engman 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other authors reported that epimastigotes incubated in saline solution did not complete the differentiation process, which was interrupted in the same intermediate stage [5]. Parasite IF were also described in cultures under the same conditions in which metacyclogenesis is induced, such as nutrient limitation [13], triatomine blood ingestion [19], presence of triatomine urine [5], modification of epimastigotes culture medium [6] and epimastigotes culture aging [7]. Disregarding the method of IF generation, they share the morphological characteristics here described; i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed as described by Tyler and Engman [13] with some modifications. Microscope slides precoated with amino-alkyl silane were used as hydrophobic surface.…”
Section: Hydrophobic Adhesion Assaymentioning
confidence: 99%
See 2 more Smart Citations